Artificial intelligence and artistic imagination: Revisiting the cultural economy of industrial revolutions - Octavian-Dragomir Jora; Mihaela Iacob; Vlad I. Roșca; Mihai-Răzvan Nedelcu; Alexandru Florin Preda; Matei-Ștefan Nedef (Amfiteatru Economic Journal, 2024)
The "economic" naturally meets the "cultural" because both spheres deal, differently albeit convergingly, with "values" and "valuations". Materially crafted and spiritually charged, tactile/tangible and ineffable/intangible, privately owned and collectively enjoyed, nourished currently and cherished diachronically, the supply of demandable cultural goods and services defines and refines us as humans. The economics of culture, notwithstanding its deeply rooted epistemological fragilities - "pricing the pricelessness" of masterpieces or fitting artistry into "production functions" -, is in greater distress when asked to predict how tech sense will affect human sensibility. Job specifications and business structures become under assail when technologies unfold, as it is the case with the Fourth Industrial Revolution (IR 4.0) and its long prophesized and still surprising Artificial Intelligence (AI). The present article aims at shedding some critical and creative light onto three lines of inquiry at the byroads of industriousness and artfulness with economics, as well as ethics. Firstly, the outstanding social-political-economic traits pertaining to the historical waves of Industrial Revolutions are re-inventoried, observing both peculiarities and patterns. Secondly, there are emphasized, although hardly exhausted, the prevailing economic reciprocations between the technological shifts and the cultural movements (in visual arts). And thirdly, given envisageable megatrends, catalysts/inhibitors and game-changers, AI's impact upon the art economy is investigated and illustrated via some emblematic cases. This study aims to open up a frontier research - the future of cultural ecosystems -, addressable/assessable as exercises of immersive foresight, and not as detached forecasting.
Keywords: O33; O55; Z11; Z13; 330; Artificial Intelligence; Industrial Revolutions; technology; digital art; cultural and creative sector; art movements; cultural economics and economy